THE DEVELOPMENT OF CORPORATE REGULATION AS A SUBJECT OF CRIMINAL LAW IN INDONESIA - M. Afrizal (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
The development of science and technology brings social changes, one of which is in the economic field, which requires the development of economic actors, from individuals to corporations. This gives rise to crimes committed by individuals or corporations. Individuals who commit crimes will face criminal penalties, but the Criminal Code does not establish criminal penalties for corporations that commit crimes. The concept of the corporation as a subject of criminal law is unclear. For this reason, this article aims to determine the basis for corporations to be subject to criminal law and to discover the development of corporate regulations as legal subjects in Indonesia. The research method used in this research is doctrinal, namely, normative legal research methods using secondary data. As criminal law subjects can be equated to human beings, the results include companies. Because it has rights and obligations imposed by the law, and because corporate talents are equated with human skills. The Draft Criminal Code, which will eventually be applied to the entire criminal law system, identifies corporations as legal subjects of criminal conduct. Consequently, any legislation outside the Criminal Code is no longer required to precisely regulate, unless the legislation outside the Criminal Code decides otherwise or deviates.